AVALIAÇÃO DA INFLUÊNCIA DE POLIMORFISMOS DA PROTEÍNA CIRCUNSPOROZOÍTA SOBRE A CARGA PARASITÁRIA E A RESPOSTA IMUNE DE INDIVÍDUOS INFECTADOS COM Plasmodium vivax. - RIBEIRO, Bruno de Paulo (2017)
Mechanisms involved in severe P. vivax malaria remain unclear. In this study, we investigated the influence of different Circumsporozoite Protein (CSP) variants on circulating plasma cytokines, parasite load and enzymes as arginase, nitric oxide synthase (NOS2) and superoxide dismutase (SOD), variables that determine the malária outcome, in individuals infected with Plasmodium vivax from a pre-Amazon area from Brazil. Samples of 25 patients infected exclusively with P. vivax and 9 healthy controls were collected and processed to obtain plasma, erythrocytes and mononuclear cells (PBMCs). Acute infection increases IL-6 and IL-10 and reduction TGF- compared to healthy controls. Only 8 patients had detectable concentrations of IFN-γ and IL-2, IL-4, TNF-, and IL-17 cytokines showed very low or undetectable concentrations in both groups. The activities of arginase and SOD were similarly increased in patients, whereas NOS2 activity, assessed indirectly by nitrite production, was unchanged relative to healthy subjects. CSP polymorphisms showed influence on the results. In addition to inducing the highest parasite loads in relation to VK210, VK247 variant also had higher concentrations of IL-6. Although IL-6 and IL-10 has been correlated in plasma, this correlation was only maintained in individuals infected with VK210. VK210 has also been shown to be related to the arginase activity increase, which may be related to the IL-10 increase induced by this variant. Polymorphisms of CSP and parasite load did not influence SOD activity. The systemic influence of the parasite was determinant for the observed profiles since all parameters of the host immune response that were altered in plasma returned to normal levels in the 48 h PBMCs culture supernatant. Finally, although increased in the patients, the production of IL- 10 followed against TGF- levels. This, associated to the increased levels of arginase, indicate that IL-10 may be produced by an alternative source in malaria. Thus, we propose that regulatory macrophages have an important role in the acute phase of vivax malaria and that CSP polymorphisms directly affect the control of the inflamed response and, consequently, the infection outcome.